1987
DOI: 10.3109/00016348709022060
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive Microsurgery of the Rabbit Oviduct Using Serosal Microsutures and Fibrin Sealant

Abstract: Microsurgical reconstruction of the rabbit oviduct was undertaken utilizing either: A: fibrin sealant in a thick layer applied to two or three serosa microsutures (20 rabbits), B: fibrin sealant only (20 rabbits), and C: microsutures only (20 rabbits). The pregnancy rates and the patency rates of the oviducts showed no significant differences between the three groups. However, the formation of adhesions at the site of reanastomosis was significantly lower and the total duration of surgery significantly shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…Ao se comparar a presença deste parâmetro entre os dois grupos, observou-se que houve uma diferença estatisticamente maior no grupo adesivo sintético, em todos os subgrupos (Figura 1). Outros autores 16,17,18,19 realizaram pesquisas com adesivo sintético e biológico nas enteroanastomoses, utilizando o mesmo animal, constataram também menor aderência nos animais do grupo adesivo biológico. Quanto a formação de deiscência, foram observados em ambos os grupos.…”
Section: Discussionunclassified
“…Ao se comparar a presença deste parâmetro entre os dois grupos, observou-se que houve uma diferença estatisticamente maior no grupo adesivo sintético, em todos os subgrupos (Figura 1). Outros autores 16,17,18,19 realizaram pesquisas com adesivo sintético e biológico nas enteroanastomoses, utilizando o mesmo animal, constataram também menor aderência nos animais do grupo adesivo biológico. Quanto a formação de deiscência, foram observados em ambos os grupos.…”
Section: Discussionunclassified
“…This procedure was executed in rabbits and compared with a pure FG anastomosis and two different suture groups. By moving the stay-sutures from the myosalpinx to the serosa and sealing with FG, postoperative tensile strength at the crucial 3-to 4-day mark was increased, and there were reductions in mucosal lesions during suturing, in adhesion formation, and in operating time [166].…”
Section: Uterine Horn/ Fallopian Tube Anastomosesmentioning
confidence: 98%
“…The tensile stress-strain value of FG anastomoses was less than that for sutured anastomoses on the third postoperative day. Therefore, Sorensen et al [166] suggested that the optimal technique for humans would be a stented anastomosis with no sutures or FG for the myosalpinx. However, two to three serosal microsutures covered with FG should be used, with the stent removed after the FG has cured for 3 min.…”
Section: Uterine Horn/ Fallopian Tube Anastomosesmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous experiments [1][2][3] have shown the technical advantages (such as re duced bleeding, reduced operation time and a significant lower adhesion formation) of using fibrin adhesive in reanastomosis of the rabbit oviduct compared to the use of conventional suturing. After a postoperative recovery of 4 weeks, the rate of pregnancy was the same in animals where the reanastomosis was per formed with the use of fibrin adhesive, autol ogous and heterologous, as in animals with PGA-sutured anastomosis and in nonoperated animals [3].…”
Section: Discussionmentioning
confidence: 99%